2002
DOI: 10.1037/0022-3514.82.5.792
|View full text |Cite
|
Sign up to set email alerts
|

It feels like yesterday: Self-esteem, valence of personal past experiences, and judgments of subjective distance.

Abstract: Supporting predictions from temporal self-appraisal theory, participants in 3 studies reported feeling farther from former selves and experiences with unfavorable implications for their current self-view than from equally distant selves and experiences with flattering implications. This distancing bias occurred when assignment to negative and positive pasts was random, for both achievement and social outcomes and for single episodes as well as longer term experiences. Consistent with a motivational interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
315
5
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(364 citation statements)
references
References 40 publications
(83 reference statements)
25
315
5
4
Order By: Relevance
“…Likewise, for Self-Esteem and Subjective Distance (Ross & Wilson, 2002), we did observe that positive past events felt closer than negative past events, but we did not replicate the moderation of this effect by self-esteem. In our view, the main effect is most vital theoretically.…”
Section: Insights About the Selected Effectscontrasting
confidence: 42%
“…Likewise, for Self-Esteem and Subjective Distance (Ross & Wilson, 2002), we did observe that positive past events felt closer than negative past events, but we did not replicate the moderation of this effect by self-esteem. In our view, the main effect is most vital theoretically.…”
Section: Insights About the Selected Effectscontrasting
confidence: 42%
“…The latter was assessed because previous studies have shown that people may feel more or less close to a past event, regardless of its actual temporal distance (Ross & Wilson, 2002). Briefly, participants were told that past experiences may feel quite close or quite far away, regardless of how long ago they actually occurred, and they were asked to rate how far away the event felt to them (1 = very close, 7 = very far away).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…However, determining the relevance of past information to present or future judgments is often ambiguous, and people may not always be motivated only by accuracy goals. In cases where people are motivated to reach a particular conclusion about how the past pertains to the present or future, they may wish to either emphasize or downplay its relevance (Peetz & Wilson, 2014;Ross & Wilson, 2002). For instance, an individual might prefer to believe that a failure does not represent an enduring deficit in his or her ability: in this instance, endorsing an implicit theory of malleability helps to support their desired conclusion.…”
Section: List Of Figuresmentioning
confidence: 99%